2002
DOI: 10.1080/03031853.2002.9523589
|View full text |Cite
|
Sign up to set email alerts
|

The New Institutional Economics: Applications for Agricultural Policy Research in Developing Countries

Abstract: This paper summarizes the potential contributions of the new institutional economics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 46 publications
4
69
0
6
Order By: Relevance
“…At the conceptual level, we developed a framework that combines concepts of New Institutional Economics (NIE) with the Agricultural Innovation System (AIS) approach. NIE stresses the crucial role of transaction costs for economic development and the concept of governance challenges used in this paper is largely based on the NIE literature (Kherallah and Kirsten 2001). NIE developed as a response to the assumption in neo-classical economics that economic agents Boperate almost in a vacuum^, which refers to an institutional vacuum (Kherallah and Kirsten 2001, p.2).…”
Section: Introductionmentioning
confidence: 99%
“…At the conceptual level, we developed a framework that combines concepts of New Institutional Economics (NIE) with the Agricultural Innovation System (AIS) approach. NIE stresses the crucial role of transaction costs for economic development and the concept of governance challenges used in this paper is largely based on the NIE literature (Kherallah and Kirsten 2001). NIE developed as a response to the assumption in neo-classical economics that economic agents Boperate almost in a vacuum^, which refers to an institutional vacuum (Kherallah and Kirsten 2001, p.2).…”
Section: Introductionmentioning
confidence: 99%
“…Van der Walt's (2005) in his study on "cooperative failures in Limpopo province observed that poor supervision, lack of training, conflict among members and inadequate funds were identified as important causative factors. Similar studies by Kherallah and Kirsten, (2002) emphasised access to start-up capital; knowledge and training in business administration, marketing and bookkeeping; low-levels of education and assertiveness towards work as the causes of non-performance of cooperatives. In many developing countries, including South Africa cattle industry is one of the largest farming enterprises.…”
Section: Background Of the Study Areamentioning
confidence: 99%
“…As cited by Kherallah and Kirsten (2001), socio-political technologies is another important variable which is expected to empower farmers, because it contributes towards reduced transaction costs and it strengthens farmers" bargaining and lobbying power. Respondents were asked whether they belonged to an organization or not and whether they sold output in groups or individually, the responses were allocated dummy values.…”
Section: Methodsmentioning
confidence: 99%